Host finding and probing behavior by Philaenus spumarius on olive varieties with a different degree of susceptibility to Xylella fastidiosa - Daniele Cornara; Valentina Zaffaroni-Caorsi; Zeinab Hamouche; Sabina Avosani; Giuseppe Cavallo; Vincenzo Verrastro; Clara Lago; Antonio Trani; Angelo De Stradis; Rodrigo P. P. Almeida; Alberto Fereres (Journal of Pest Science, 2024)
Abundance on and access time to the host plant are the pivotal factors in Xylella fastidiosa transmission to olive by the meadow spittlebug Philaenus spumarius . Therefore, olive varieties suitable for the vectors, i.e., plants providing all the necessary cues to the insect for their location, settling and acceptance, and devoid of antixenotic defenses, could be more susceptible to infection than varieties non- or less suitable for the vector. Here we evaluated whether a bacterium-susceptible olive variety, Ogliarola Salentina, could be a more suitable host for P. spumarius than the two resistant varieties Leccino and FS-17. We carried out: (i) an evaluation of between-hosts and within-host preference; (ii) an insect survival analysis; (iii) an Electrical Penetration Graph (EPG)-assisted analysis of the probing behavior; (iv) light microscopy of the tissues the spittlebugs had access to; (v) an analysis of the xylem sap primary metabolites. In choice tests, the insect exhibited a significant preference for Ogliarola Salentina. In addition, spittlebugs displayed longer xylem sap ingestion bouts on the bacterium-susceptible variety compared to resistant genotypes, possibly because of differences in the xylem sap chemical profile rather than xylem anatomy. Spittlebugs preference for Ogliarola over both Leccino and FS-17 could be a relevant and so far overlooked component of the low disease prevalence in these two olive varieties reported in Southern Italian olive orchards. Overall, our data point toward the importance of incorporating studies on vector-plant interaction and host traits of resistance to the vector in research on genotypes resistant to X. fastidiosa .